Business and Intellectual Capital Development in Financial Riptide - Case Studies of Finnish Biotechnology and Pharmaceutical Companies Dispersing into Global Value Chains - Martti Kulvik; Marja Tähtinen; Pekka Ylä-Anttila (The Research Institute of the Finnish Economy (ETLA), 2013)
This study focused on two primary areas: 1. To determine what can be learned from biotech and drug development companies that suffered from financial problems and ultimately failed at the beginning of the 21st century. 2. To determine how intellectual capital developed in accordance with such companies and its fate following business failure. We examined six failed Finnish biotechnology companies and two major venture capital companies that have invested in Finnish biotechnology companies. We strongly emphasize that this research is only a case-based and very limited feasibility study. Nevertheless, the results were surprising. We found that intellectual capital was indeed created in the companies and that various aspects of this capital could be identified. To a certain extent, we were also able to follow the post-company steps of intellectual capital and the continuity of its value-creation in novel companies. The study was designed to involve only failed companies, but in four cases we found ourselves interviewing leaders of companies that had been created based on the IC of failed companies. It appears that important knowledge has vested by learning from earlier mistakes, and this learning period has created important intellectual capital that has already been exploited by various companies. Research-intensive companies typically operate in fields where failure is an inherent risk. Governments typically support emerging industries based on high-technology because of their growth potential. The combination of high-intensity R&D and high risks creates a problem for all investors. The created value is primarily in the form of intangible assets, which are not captured in traditional accounting and for which no well-established alternative metrics exist. Consequently, in the case of a company failure, most of the created value added is considered lost. This loss not only complicates the justification of government support policies but typically leads to high initial expectations of the sector that are unfortunately often followed by subsequent disappointments. We think that the present concept of failure may be profoundly misleading.
Keywords: G24; G33; J24; L65; M13; O32; 330; Intellectual capital; Biotechnology companies; Life science; Knowledge recycling; Venture capital; Failed companies; Biotechnologie-Industrie; Pharmaindustrie; Immaterielle Werte; Risikokapital; Insolvenz; Finnland